Aristotle on the Nature and Causes of Perception - Roreitner, Robert (Cambridge University Press, 2026)
This book provides a fresh interpretation of Aristotle's account of perception, refocusing the debate and emphasising what remains philosophically relevant. It will engage experts on Aristotle and help those who work in ancient philosophy, including advanced students, while inviting contemporary philosophers to engage with Aristotle's thought.